2021
DOI: 10.1080/23273798.2021.1994620
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic priming across highly similar languages is not affected by language proficiency

Abstract: This study explores the mechanism underlying shared syntactic representations for highly similar languages by investigating whether cross-linguistic syntactic priming is affected by language proficiency. In two experiments, native (L1) Mandarin-Chaoshanese speakers with moderate proficiency in Cantonese (L2) heard Chaoshanese and Cantonese dative sentences with a prepositional object (PO) or a double object (DO) structure, and then completed a description of a depicted ditransitive event using Mandarin. Primin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…For instance, Bernolet and colleagues (2013) correlated the magnitude of structural priming effects with L2 pro ciency and observed that crosslinguistic priming effects became larger with increasing pro ciency, whereas within-L2 priming effects in the presence of lexical overlap became smaller as pro ciency increased. On the other hand, a recent study that investigated priming between Cantonese and Mandarin did not observe any effect of pro ciency (Liu et al, 2022), which suggests that pro ciency has no effect on the sharing of syntax between highly similar languages.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For instance, Bernolet and colleagues (2013) correlated the magnitude of structural priming effects with L2 pro ciency and observed that crosslinguistic priming effects became larger with increasing pro ciency, whereas within-L2 priming effects in the presence of lexical overlap became smaller as pro ciency increased. On the other hand, a recent study that investigated priming between Cantonese and Mandarin did not observe any effect of pro ciency (Liu et al, 2022), which suggests that pro ciency has no effect on the sharing of syntax between highly similar languages.…”
Section: Introductionmentioning
confidence: 76%
“…Interestingly, cross-linguistic structural priming has been observed with a wide variety of language pairs, such as English-Dutch (Bernolet et al, 2007(Bernolet et al, , 2013; Desmet & Declercq, 2006;Schoonbaert et al, 2007), English-French (Hartsuiker et al, 2016), English-Polish (Fleischer et al, 2012), English-Mandarin (Chen et al, 2013;Huang et al, 2019), English-Korean (Hwang et al, 2018;Shin & Christianson, 2009;Song & Do, 2018), English-Irish (Favier et al, 2019), English-Swedish (Kantola & van Gompel, 2011), English-Spanish (Flett et al, 2013;Hartsuiker et al, 2004), Cantonese-Mandarin (Cai et al, 2011;Huang et al, 2019;Liu et al, 2022), Dutch-German (Bernolet et al, 2007), Dutch-French (Hartsuiker et al, 2016), and Spanish-Swedish (Montero-Melis & Jaeger, 2020) (see Muylle et al, 2023, for an overview of studies). Some of these studies found that structural priming patterns may differ across L2 pro ciency levels (e.g., Bernolet et al, 2013;Favier et al, 2019;Hartsuiker & Bernolet, 2017; Kim & McDonough, 2008; Montero-Melis & Jaeger, 2020), although the direction of the effect seems to depend on whether there is lexical overlap between prime-target pairs or not.…”
Section: Introductionmentioning
confidence: 99%
“…Syntactic knowledge, which is involved in the four language skills that we measured, is arguably the type of knowledge that is the most likely to affect the magnitude of structural priming in L2 speakers since priming tasks evaluate the production of syntactic structures. Previous studies have similarly observed that self-reported proficiency predicted priming magnitude (Bernolet et al, 2013;Hartsuiker & Bernolet, 2017; but see Liu et al, 2021) and in fact, to our knowledge, most L2 structural priming studies have used such selfreports to assess the effect of proficiency on priming (Kim & McDonough, 2008).…”
Section: Assessing the Effect Of Proficiencymentioning
confidence: 84%
“…We also asked the participants to rate their French proficiency for reading, speaking, writing, and listening skills on a Likert scale that ranged from 1 ( not proficient at all ) to 7 ( very proficient ). We calculated self‐rated proficiency by averaging these four self‐ratings (for similar measures of proficiency, see Bernolet et al., 2013; Favier et al., 2019; Hartsuiker & Bernolet, 2017; Liu et al., 2021). Independent‐samples t tests revealed that the low proficiency group who had learned French somewhat later in life had read fewer books2 in French and rated themselves less proficient in French than did the high proficiency group ( p s < .05).…”
Section: Methodsmentioning
confidence: 99%